Repair and structural performance of initially cracked reinforced concrete Slabs - Thanoon, Waleed Abdulmalik; Jaafar, Mohd Saleh; Abdul Kadir, Mohd Razali; Noorzaei, Jamaloddin (Elsevier, 2005)
Crack is one of the most common defects observed in reinforced concrete slabs and beams. Major cracks in concrete structures may occur due to overloading, corrosion of reinforcement or differential settlement of support. To restore the structural capacity of the distressed elements, retrofitting and/or strengthening are needed. There are different techniques available for retrofitting and strengthening of different reinforced concrete structural elements reported in the literature. This paper investigates the structural behaviour of cracked reinforced concrete one-way slab, which is repaired using different techniques.